INVENTORY OF USEFUL PLANT SPECIES IN BOSNIA AND HERZEGOVINA (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
For the purposes of the inventory, an analysis of 55 literature sources of useful plant species in the households of the population of Bosnia and Herzegovina was performed. A total number of 748 plant species have been identified. According to the taxonomy, they are classified into 112 families and 418 genera. The most numerous families within which useful species are cited are: Compositae, Rosaceae, Lamiacae, Apiacae, Brasicaceae, Ranunculaceae and Poaceae. The useful species are mostly used in treatment and nutrition. Some of them are also used in the production of drugs, so they are described in pharmacopoeias such as: the Yugoslav Pharmacopoeia (2000) describing 88 species, the WHO’s monographs on medicinal plants describing 62 species, the European Pharmacopoeia (8th edition) with 79 plants. Useful species with the most citations in the literature are: Urtica dioica, Hypericum perforatum, Althaea officinalis, Juniperus communis and Sambucus nigra. Bosnia and Herzegovina is a country with a high diversity of useful plants and significant potential that can be used in the future. A large number of publications indicate that the population throughout history has used biodiversity and natural resources in a traditional and sustainable way. The results are the basis for future research on sustainable management, promotion of natural values, useful plants and and conservation of biodiversity in BiH.